CONTENT MARKETING AND CUSTOMER REVIEW AS INFLUENTIAL FACTORS IN CONSUMER PURCHASING DECISIONS A TIKTOK SHOP, CASE STUDY IN SRIWINANGUN, CIAMIS REGENCY - Sri Ayu Lestari; Hendi Sobari; Siti Amirah Makarim (LP2M Universitas Perjuangan Tasikmalaya, 2025)
Digital transformation has changed society's consumer behavior, including the growing interest in shopping through e-commerce platforms like TikTok Shop. In this context, content marketing and customer reviews are two important aspects that influence purchasing decisions. The objective of this research study is to investigate the influence of content marketing and customer reviews on the purchasing decisions of TikTok Shop users in Kampung Sriwinangun, Kabupaten Ciamis. The study was conducted using a descriptive-quantitative approach, with data collected from 85 respondents via questionnaire. The results of the correlation coefficients show that each variable has a strong relationship. The results of the regression analysis also show that both variables, both individually and jointly, have a positive and significant influence on purchasing decisions. This means that engaging marketing content and compelling customer reviews can positively influence consumers' purchasing decisions.